2008
DOI: 10.2174/1874945300801010005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Physical Assault on Dating Partners

Abstract: This paper examines the prevalence and correlates of dating partner violence in a cohort of 1,736 university students from Hong Kong and the United States. The participants completed the Revised Conflict Tactics Scale and the Personal and Relationships Profile to report on the rates of occurrence of physical assault and injury. The differences between the two sites were compared using independent t-tests. Logistic regression was employed to predict the presence or absence of physical assault in the previous ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 42 publications
3
19
0
1
Order By: Relevance
“…The CBT programs determined to have been the most effective in reducing IPV recidivism feature stress reduction components in their curriculum (Babcock et al, 2004;Eckhardt et al, 2013 Research: Given the lack of correlation between male perpetrators' sexist, traditional sex role beliefs and IPV perpetration (Sugarman & Frankel, 1996), the Duluth focus on patriarchy and gender roles appears to be misplaced. However, the same authors determined in their meta-analysis that pro-violent attitudes do in fact predict relationship violence, findings also reported by Capaldi et al (2012) in their review of the literature and by the National Family Violence Survey (Chan & Straus, 2008). Furthermore, identifying, disputing, and altering cognitive distortions irrational beliefs of all types is a central component of effective CBT programs (Babcock et al, 2004;Eckhardt et al, 2013 (Stosny, 1995).…”
Section: Group Format and Curriculummentioning
confidence: 94%
“…The CBT programs determined to have been the most effective in reducing IPV recidivism feature stress reduction components in their curriculum (Babcock et al, 2004;Eckhardt et al, 2013 Research: Given the lack of correlation between male perpetrators' sexist, traditional sex role beliefs and IPV perpetration (Sugarman & Frankel, 1996), the Duluth focus on patriarchy and gender roles appears to be misplaced. However, the same authors determined in their meta-analysis that pro-violent attitudes do in fact predict relationship violence, findings also reported by Capaldi et al (2012) in their review of the literature and by the National Family Violence Survey (Chan & Straus, 2008). Furthermore, identifying, disputing, and altering cognitive distortions irrational beliefs of all types is a central component of effective CBT programs (Babcock et al, 2004;Eckhardt et al, 2013 (Stosny, 1995).…”
Section: Group Format and Curriculummentioning
confidence: 94%
“…In practice, the Duluth Model also rejects as excuses rather than real causes almost all the many other risk factors identified by hundreds of studies and summarized in the World Health Organization report cited in the previous section. Many of these risk factors can be identified using the Personal and Relationships Profile (Chan & Straus, 2008;Straus, Hamby, Boney-McCoy, & Sugarman, 2010). This instrument measures 25 variables that have been demonstrated in research to be associated with an increased probability of partner violence, including of course dominance by one partner.…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…In their sample of 997 abusive men, Hanson, Cadsky, Harris, and Lalonde (1997) found that severely abusive men score higher on measures of attitudes tolerant of spouse assault than nonabusive men, and the most severely abusive men had higher scores than the less abusive men. A cross-cultural study found that both men and women in the United States were more than 3 times more likely to perpetuate relationship violence if they have an attitude of violence approval (Chan & Straus, 2008). A large scale study of 13,837 couples from six African countries found that measures of attitudes in support of spousal violence were significantly associated with violence in all but one African nation in the analysis (Alio et al, 2011).…”
Section: Applying the Need Principle To Domestic Violence Programsmentioning
confidence: 99%